One-dimensional porous La0.5Sr0.5CoO2.91 nanotubes as a highly efficient electrocatalyst for rechargeable lithium-oxygen batteries. (20th May 2015) - Li, Pengfa; Zhang, Jiakai; Yu, Qilin; Qiao, Jinshuo; Wang, Zhenhua; Rooney, David; Sun, Wang; Sun, Kening
Abstract: The electrochemical performance of one-dimensional porous La0.5 Sr0.5 CoO2.91 nanotubes as a cathode catalyst for rechargeable nonaqueous lithium-oxygen (Li-O2 ) batteries is reported here for the first time. In this study, one-dimensional porous La0.5 Sr0.5 CoO2.91 nanotubes were prepared by a simple and efficient electrospinning technique. These materials displayed an initial discharge capacity of 7205 mAh g −1 with a plateau at around 2.66 V at a current density of 100 mA g −1 . It was found that the La0.5 Sr0.5 CoO2.91 nanotubes promoted both oxygen reduction and oxygen evolution reactions in alkaline media and a nonaqueous electrolyte, thereby improving the energy and coulombic efficiency of the Li-O2 batteries. The cyclability was maintained for 85 cycles without any sharp decay under a limited discharge depth of 1000 mAh g −1, suggesting that such a bifunctional electrocatalyst is a promising candidate for the oxygen electrode in Li-O2 batteries.